Co-occurrence of antimicrobials and metals as potential drivers of antimicrobial resistance in swine farms - Congilosi, Jena L.; Wallace, Joshua S.; Neher, Timothy P.; Howe, Adina; Soupir, Michelle L.; Aga, Diana S. (Frontiers in Environmental Science, 2022)
The application of animal manures to cropland is an important nutrient recycling strategy in many parts of the world. Commonly, aggregated manure wastes contain chemical stressors including veterinary antimicrobials, heavy metals, and antimicrobial resistance genes (ARGs) that can stimulate the development and proliferation of antimicrobial resistance (AMR). While the presence of antimicrobials in manure is well-documented, the co-occurrence of other potentially impactful chemical stressors in swine manure remains underreported. This study quantifies and analyzes correlations between antimicrobials, metals, and certain ARGs present in manure samples from swine farms in Iowa, USA. Relationships between chemical stressors and different stages of swine production or feed composition are also investigated. Results revealed substantial levels of tetracyclines (up to 1,260 µg g-1 dry weight (d.w.) of manure for oxytetracycline) detected in all samples. Tiamulin, two ionophores (monensin and lasalocid), and one macrolide (tilmicosin) were detected at maximum class concentrations of 9.4, 0.547, and 0.472 µg g-1 d.w., respectively. The median relative abundances of ermB and tetM were 0.13 and 0.17 copies g-1 wet weight (w.w.) manure (normalized to 16S gene), respectively. Additionally, high levels of copper (Cu), iron (Fe), and zinc (Zn) were detected in all samples, with maximum concentrations of 887, 1,900, and 2,100 µg g-1 d.w., respectively. Notably, uranium (U) was detected in 11 samples, at concentrations up to 0.77 µg g-1. A global analysis of AMR-stressor relationships using Spearman's rank correlation indicates Cu, and Ba are the most positively and significantly correlated with cytotoxic anhydrotetracycline (ATC) and/or anhydrochlortetracycline (ACTC) concentrations in all tested facilities (Cu-ATC: ρ = 0.67, p = 0.0093; Cu-ACTC: ρ = 0.75, p = 0.0022; Ba-ATC: ρ = 0.84, p = 0.0002). Interestingly, ermB and tetM genes were strongly, positively correlated to each other (ρ=0.92, p= 0.000), suggesting possible co-selection, despite the absence of correlation between ARGs and tetracycline concentrations. This study demonstrates the complexity of interactions between antimicrobials, metals, and ARGs in multiple manure storage pits prior to cropland application.